Differential susceptibility to endocrine disruptor-induced epimutagenesis. Issue 1 (8th December 2020) - Lehle, Jake D; McCarrey, John R
Abstract: There is now considerable evidence indicating the potential for endocrine disrupting chemicals to alter the epigenome and for subsets of these epigenomic changes or "epimutations" to be heritably transmitted to offspring in subsequent generations. While there have been many studies indicating how exposure to endocrine disrupting chemicals can disrupt various organs associated with the body's endocrine systems, there is relatively limited information regarding the relative susceptibility of different specific organs, tissues, or cell types to endocrine disrupting chemical-induced epimutagenesis. Here we review available information about different organs, tissues, cell types, and/or cell lines which have been shown to be susceptible to specific endocrine disrupting chemical-induced epimutations. In addition, we discuss possible mechanisms that may be involved, or impacted by this tissue- or cell type-specific, differential susceptibility to different endocrine disrupting chemicals. Finally, we summarize available information indicating that certain periods of development display elevated susceptibility to endocrine disrupting chemical exposure and we describe how this may affect the extent to which germline epimutations can be transmitted inter- or transgenerationally. We conclude that cell type-specific differential susceptibility to endocrine disrupting chemical-induced epimutagenesis is likely to directly impact the extent to, or manner in, which endocrine disrupting chemical exposure initially induces epigenetic changes to DNA methylation and/or histone modifications, and how these endocrine disrupting chemical-induced epimutations can then subsequently impact gene expression, potentially leading to the development of heritable disease states.